Can the U.S. remain an attractive host for FDI in the auto industry? New labor policy and flexible production - Terutomo Ozawa (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
The author argues that the proposed EFCA, if enacted, would decrease the attractiveness of the United States for FDI in the auto industry.
Keywords: 330